2012
DOI: 10.1111/j.1532-5415.2011.03803.x
|View full text |Cite
|
Sign up to set email alerts
|

Using the Nintendo Wii as an Intervention in a Falls Prevention Group

Abstract: Several possible mechanisms could explain the protective role of PA against disability. For instance, PA promotes healthy behaviors through self-motivation and better-functioning social networks, which in turn contribute to maintaining good health and avoiding disability. Alternatively, PA could affect health through physiological changes; with people expressing PA being better able to cope with stressful situations and therefore maintaining less-damaging neuroendocrine and immunological patterns. 10 The pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…In rehabilitation, exergaming has been used as a tool to improve balance and functional movement in a variety of populations. [3][4][5][6][7][8] One of the main reasons for employing video games is the ability to increase motivation and produce a distraction ( Figure 3) from mundane and boring training and/or painful treatments. 9 It is interesting to note that when an earlier review of exergaming was published there were no studies carried out in people with multiple sclerosis (PwMS), 1 even though it is possible that the reported benefits of exergaming in balance and mobility in other populations will have a positive impact on PwMS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rehabilitation, exergaming has been used as a tool to improve balance and functional movement in a variety of populations. [3][4][5][6][7][8] One of the main reasons for employing video games is the ability to increase motivation and produce a distraction ( Figure 3) from mundane and boring training and/or painful treatments. 9 It is interesting to note that when an earlier review of exergaming was published there were no studies carried out in people with multiple sclerosis (PwMS), 1 even though it is possible that the reported benefits of exergaming in balance and mobility in other populations will have a positive impact on PwMS.…”
Section: Introductionmentioning
confidence: 99%
“…9 It is interesting to note that when an earlier review of exergaming was published there were no studies carried out in people with multiple sclerosis (PwMS), 1 even though it is possible that the reported benefits of exergaming in balance and mobility in other populations will have a positive impact on PwMS. [3][4][5][6][7][8] This review will describe some of the key exergame research to promote physical activity and its use in rehabilitation in The use of gaming technology for rehabilitation in people with multiple sclerosis other diseases or clinical populations. We will then describe the current state of research in exergaming in PwMS and describe the theories for the mechanism behind some of the improvements in outcomes seen after using exergaming.…”
Section: Introductionmentioning
confidence: 99%
“…1 The Wii Fit has been used as a tool to aid rehabilitation in patients with, for example, cerebral palsy, 2 stroke, 3 and falls. 4 The improvements to functional clinical outcomes have been marked. For example, in elderly fallers our earlier work has shown that training that incorporates the Wii Fit as an adjunct to traditional training improves timed up-and-go, 10-m walk time/ speed, flexibility, and psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in elderly fallers our earlier work has shown that training that incorporates the Wii Fit as an adjunct to traditional training improves timed up-and-go, 10-m walk time/ speed, flexibility, and psychological well-being. 4 Patients in our clinic anecdotally report the Wii Fit as being fun. Active gaming systems primarily are a form of entertainment and not a rehabilitation tool.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation